Vocal characteristics of pygmy blue whales and their change over time - Gavrilov, Alexander; McCauley, Robert; Salgado Kent, Chandra; Tripovich, J.; Burton, C. (Acoustical Soceity of America, 2011)
Vocal characteristics of pygmy blue whales of the eastern Indian Ocean population were analyzed using data from a hydroacoustic station deployed off Cape Leeuwin in Western Australia as part of the Comprehensive Nuclear-Test-Ban Treaty monitoring network, from two acoustic observatories of the Australian Integrated Marine Observing System, and from individual sea noise loggers deployed in the Perth Canyon. These data have been collected from 2002 to 2010, inclusively. It is shown that the themes of pygmy blue whale songs consist of ether three or two repeating tonal sounds with harmonics. The most intense sound of the tonal theme was estimated to correspond to a source level of 179 ± 2 dB re 1 μPa at 1 m measured for 120 calls from seven different animals. Short-duration calls of impulsive downswept sound from pygmy blue whales were weaker with the source level estimated to vary between 168 to 176 dB. A gradual decrease in the call frequency with a mean rate estimated to be 0.35 ± 0.3 Hz/year was observed over nine years in the frequency of the third harmonic of tonal sound 2 in the whale song theme, which corresponds to a negative trend of about 0.12 Hz/year in the call fundamental frequency.